Adentrando o labirinto da classificação de assunto: uma discussão sobre o universo temático dos mangás com base em enredos da Wikipedia - Teixeira, Joyce Ribeiro (Brasil, 2022)
The present work weaves a discussion about the activity of classification of subjects, having as a background the manga as informational material. This is a Completion Work for the Bachelor's Degree in Librarianship. Its main objective is to understand to what extent the subject classification actions reflect the thematicity of manga, considering this a serious problem from the point of view of information organization. It is justified in the lack of works of the same nature, and in the attempt to discuss updates of consolidated activities within the field of Librarianship, which need to meet the new formats of documents that integrate the collections of libraries. In order to do so, it uses the method of content analysis to index and examine Wikipedia's contents of the 50 best manga of all time, according to the Ranker website. As main results, the work points to a very clear difficulty in the classification activity when it comes to manga, which by traditional means is not able to contemplate the thematicity of the content addressed in the stories. It is expected, therefore, that this research fosters new discussions about these issues, in order to guarantee more relevant alternatives to the precision in the classification of manga subjects, thus providing their recoverability in information systems and online catalogs.